The Effect of Using Genre-Based Learning Method on Students’ Writing Descriptive Text at SMPN 1 Paranginan - Widya, Widya Siburian; Tampubolon, Sahlan; Napitupulu, Fenty Debora (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2024)
This research aims to determine the effect of using the Genre-based learning method on students' writing ability. This research was prepared using quantitative experimental research with a sample of class IX students at SMP N 1 Paranginan. The number of samples in this study was 40 students and was divided into two classes, namely the experimental class and the control class. The data collection instrument uses a writing test and the data collection technique uses a pre-test and post-test, while data was analyzed by using T-test Formula. From the research that has been conducted, it was found that there was a significant difference between the pre-test and post-test. In the experimental class, the score was 53,05 and the post-test score was 81.4, while in the control class, the pre-test score was 56,1 and the post-test score was 80.95. So, it can be concluded that the use of the genre-based learning method has a great influence on improving students' writing skills at SMP N 1 Paranginan.